IMPLEMENTATION OF BCRYPT ALGORITHM ON WEBSITE-BASED HASHING GENERATOR USING LARAVEL FRAMEWORK - Febrian, Dio; Christian, Yoel; Sutisna, Alifan Widad; Budiarto, Gunawan; Syukur, Muhammad; Ramadhan, Xena Hadi; Kuntoro, Antonius Yadi; Fahlapi, Riza (Journal of Information System, Informatics and Computing; Vol 7 No 2 (2023): JISICOM (December 2023)DO - 10.52362/jisicom.v7i2.1130, 2023)
Implementation of the Bcrypt algorithm on a website-based hashing generator using the Laravel framework has been carried out in this study. The background of this research is based on the development of information technology which has affected many aspects of human life, where data and information are very important and need to be protected. Web-based information systems are vulnerable to security threats, such as wiretapping and intrusion by unauthorized parties. Therefore, the implementation of information security aims to overcome these problems and provide solutions both technically and non-technically. This research uses the Laravel framework, an open-source PHP framework that enables the development of web applications with modules that optimize PHP performance. Bcrypt and salt algorithms are used in the hashing process to protect user data. The results of the research show that using Laravel as the right framework for making hashing generators. The result of the hashing process produces a constant value of 60 characters, even if the input text is more than 60 characters with random text. The cost factor, which is a factor that regulates hashing power, affects the time required for the hashing process and hash verification. Using the Bcrypt generator tool is useful in cross-browser testing, especially in tests involving hashed passwords. With this tool, many valid bcrypt password hashes can be generated for testing. This research makes an important contribution in improving the security of web-based information systems by applying the Bcrypt algorithm to the hashing process. This implementation can provide better data protection for users and improve overall system performance.